LIS-3 REGISTER OF THE ACUTE CORONARY SYNDROME: WHAT HAS CHANGED IN A "PORTRAIT" OF A PATIENT AND SHORT-TERM OUTCOMES OF THE DISEASE COMPARED TO LIS-1 REGISTER - S. Yu. Martsevich; Y. V. Semenova; N. P. Kutishenko; M. L. Ginzburg; A. V. Zagrebelnyy; A. V. Fokina; E. V. Daniels (Столичная издательская компания, 2017)
Aim. To compare a «portrait» of a patient and hospital lethality between register LIS-1 of myocardial infarction (MI) and register LIS-3 of acute coronary syndrome (ACS).Material and methods. We compared two registers held in Lubertsy town: MI register LIS-1 (2005-2007) and ACS register LIS-3 (01.11.2013-31.07.2015). LIS-1 is a retrospective study; information about patients survived and died in hospital was taken from medical histories. LIS-3 is a prospective study; data on survived patients was collected from questionnaires and medical histories, information about died ones - from medical histories.Results. «Portrait» of a patient of LIS-1 and LIS-3 registers was comparable in gender, age, history of MI, arterial hypertension, atrial fibrillation, and stroke. LIS-3 patients had diabetes mellitus more often, and on the contrary, history of ischemic heart disease (IHD) and angina pectoris - more rarely than  LIS-1 patients. ACS was the first manifestation of IHD in 64% of LIS-3 register patients and 31.4% of LIS-1 register patients. Hospital lethality was 15.2% in LIS-1 register and 19.4% in LIS-3 register (p>0.05). Hospital lethality increased in elderly patients in both  registers. Atrial fibrillation increased hospital lethality risk in LIS-3 register and long-term mortality risk in LIS-1 register. History of arterial hypertension and angina pectoris re duced hospital lethality risk in LIS-3 register. In LIS-1 register neither of these factors was significant, but left ventricular hypertrophy reduced hospital mortality risk.Conclusion. LIS-1 and LIS-3 patients were comparable in many factors, bud differed in history of IHD (31.4% in LIS-1 register, 64% in LIS-1 register) and angina pectoris. Factors associated with hospital mortality differed in the two registries.